Unraveling the Origin of Dark Current in Organic Bulk Heterojunction Photodiodes for Achieving High Near-Infrared Detectivity - Go, Enoch; Jin, Hyunjung; Yoon, Seongwon; Park, Sungmin; Park, So Hyun; Yu, Hyeonggeun; Son, Hae Jung (American Chemical Society, 2022)
Organic infrared materials are attractive due to their high absorption coefficients and facile tuning of the absorption spectrum beyond that of silicon. Although bulk heterojunctions (BHJs) are widely used in organic photodetectors (OPDs), achieving a high signal-to-noise ratio in the near-infrared spectrum is often challenging due to the inherently large dark currents in low-bandgap polymers and their blending morphology effect. Herein, we investigate the origin of dark currents in near-infrared OPDs and reveal a strategy to improve the detectivity in terms of two aspects: (1) donor-acceptor blending morphology and (2) effects of carrier injection from outer electrodes. To do so, a series of random terpolymers were synthesized in a similar band structure and their blending morphology with the PC71BM acceptor was gradually controlled. As the phase separation was smaller, the dark current gradually reduced while the responsivity increased, leading to a higher detectivity. Complex charge-transporting paths formed under the fine percolating network account for the dark current reduction, while the increased heterojunction area facilitates the dissociation of the photogenerated excitons. From our thermal admittance spectroscopy, deeper sub-bandgap states were found under the smaller phase separation, further contributing to the dark current reduction. Second, the carrier injection effect was revealed by inserting a charge-blocking layer at the active layer/electrode interface. While manipulating both parameters could yield a high near-infrared detectivity up to 10(12) Jones at -0.5 V, the blending morphology effect turns out to be more dominant over the carrier injection effect in suppressing the dark current and achieving higher detectivity in BHJ OPDs.